Kendali Supply Beban Pada Sistem Pembangkit Hybrid - Abdillah, Hartawan; Afandi, A.N.; Qurrata Ayun, Aldilla; Ari wibowo, Sulton (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2020)
The Solar Power Plant is hybridized with other generating systems, namely the Wind Power Plant is one of the promising alternative energies in Indonesia. Power plant hybridization is using two or more power plants with different energy sources. Generally combined and supplied with PLN or Genset, in order to obtain synergies that provide economic and technical benefits (reliability of the supply system). The hybrid generator will maximize its use if supported by its load control. Use of efficient electrical energy is balanced with the use of the load released. Hybrid plants will not occur. Based on tests that have been carried out the intensity of sunlight affects the power produced by solar cells. The highest sunlight intensity when testing is during the day at 567 Lux with a voltage value of 21.22 V and current of 0.30 A, while the lowest intensity of sunlight is at 17.00 with the intensity of sunlight 56 ​​Lux with a voltage value of 5.5 V and current 0.15 A